« The Fault is that she is my wife » : L’ambivalence des représentations d’Henriette-Marie (1625-1649) - Alice Leroy (Sillages Critiques)
Many historians have focused on Charles I, his reign but his representations. Their impact within the context of his personal rule and of the Civil Wars, leading up to the Regicide, has been the object of many studies, yet what can be said of the image of his wife? This paper examines the representations of Henrietta Maria, the French Catholic princess he married, and the influence they held over the king’s own image. While her very presence reinforced the trope of Charles I as husband to the nation and father to his people, she also became a source of anxiety at a period when popery and the very institution of the monarchy came under violent attack from a part of the English people.